An Open Clinical Trial To Evaluate The Combined Effect Of Dashamoola Kashaya Adhokayaseka, Astakatvar Taila Matra Basti & Kamsakhya Guggulu In The Management Of Gridhrasi With Special Reference To Sciatica - Minajagi, Namita; Kalyani, S S (International Research Journal of Ayurveda & Yoga, 2020)
Gridhrasi is one among the Shoola Pradhana Vataja Nanatmaja Vyadhi, intervening with the functional ability of low back and lower limbs. Low back pain is the major cause of morbidity throughout the world affecting mainly young adults. This is a Combined Clinical Study of Dashamoola Kashaya Adhokayaseka, Astakatvara Taila Matra Basti and Kamsakhya Guggulu. In the present study total 30 patients having Gridhrasi were included. Patients were selected randomly from the OPD and IPD of BVVS Ayurved Hospital, Bagalkot. Case Performa was prepared with all points of history taking, physical examination and X-ray to confirm the diagnosis as mentioned in our classics and modern science. Management-1]Dashamoola Kashaya Adhokayaseka 30 minutes for 8 days. 2]Astakatvara Taila Matra Basti 48ml for 8 days. 3]Kamsakhya Guggulu 1gm/day for 30 days after food. Results and Concliusion – Dashamoola Kashaya Adhokayaseka, Astakatvara Taila Matra Basti and Kamsakhya Guggulu have significant therapeutic value in Gridhrasi.